Belajar Bersama Untuk Meningkatkan Kemampuan Anak - Praktikan Putri; Tuti Atika (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Field work practice activities are carried out to directly practice the material that has been studied so far, this activity is also carried out as a means for students to meet directly with clients and be able to assist clients in solving problems using methods and stages that have been studied previously. The activity was carried out at the Cahaya Hati Anugerah Indonesia Foundation Orphanage, where some of these children did not receive guidance in learning, which caused them to have difficulty understanding the subject matter. Related to this problem, the effort that can be done to solve this problem is to carry out mini project activities using the learning by discussion method through various stages consisting of Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and Termination. The problem solving process applied to clients is a way to make it easier for clients to exchange ideas when studying with friends. It is hoped that with the implementation of this program clients can be even more enthusiastic about carrying out learning activities so they are not left behind with other friends.